The Power of Music to Prevent and Control Emerging Infectious Diseases - Benavides, Julio A.; Caparrós, Cristina; da Silva, Ramiro Monã; Lembo, Tiziana; Tem Dia, Philip; Hampson, Katie; Dos Santos, Feliciano (Frontiers in Medicine, 2021)
Music is a powerful approach to engage communities and disseminate information. Specifically, health campaigns employing music have been used to promote behaviors that can prevent emerging infectious diseases (EIDs). For example, hip hop artists supported campaigns to prevent acquired immunodeficiency syndrome in the 70s in the United States, while Brazilian funk promoted vaccination to mitigate the ongoing COVID-19 pandemic. Similarly, we broadcast musical messages in local languages to increase community awareness and support prevention measures in Guinea and Liberia in response to the recent Ebola outbreak in 2021. Given the potential of music to promote both individual and population-level behavioral changes to prevent transmission, there is a need to consolidate information on music-based health interventions, and on how we can measure their effectiveness. In this perspective, we provide examples of relevant initiatives, discussing challenges and solutions associated with implementing interventions based on our experience with the 2021 Ebola outbreak. We recommend four steps for a successful music-based health intervention including (1) establishing a task force, (2) compose a “catchy” song including critical preventive measures, (3) deliver the song to the target audience, and (4) evaluate the campaign effectiveness. We argue that close interactions between scientists and musicians can produce rapid musical content for disease prevention. We also identify and discuss several methodological frameworks for testing the effectiveness of such interventions. We conclude that support from public health authorities, government media departments, and international agencies, is necessary to deliver wide outreach and long-term sustainability of musical messaging toward effective EID prevention.